"Meaningful Use" of EHR in Dental School Clinics: How to Benefit from the U.S. HITECH Act's Financial and Quality Improvement Incentives. Issue 4 (1st July 2012) - Kalenderian, Elsbeth; Walji, Muhammad; Ramoni, Rachel B.
Abstract : Through the 2009 HITECH (Health Information Technology for Economic and Clinical Health) Act, the U.S. government committed $27 billion to incentivize the adoption and "meaningful use" of certified electronic health records (EHRs) by providers, including dentists. Given their patient profiles, dental school clinics are in a position to benefit from this time‐delimited commitment to support the adoption and use of certified EHR technology under the Medicaid‐based incentive. The benefits are not merely financial: rather, the meaningful use objectives and clinical quality measures can drive quality improvement initiatives within dental practices and help develop a community of medical and dental professionals focused on quality. This article describes how dentists can qualify as eligible providers and the set of activities that must be undertaken and attested to in order to obtain this incentive. Two case studies describe the approaches that can be used to meet the Medicaid threshold necessary to be eligible for the incentive. Dentists can and have successfully applied for meaningful use incentive payments. Given the diverse set of patients who are treated at dental schools, these dental practices are among those most likely to benefit from the incentive programs.